Butyric Acid Increases the Therapeutic Effect of EHLJ7 on Ulcerative Colitis by Inhibiting JAK2/STAT3/SOCS1 Signaling Pathway - Tang, Xiaonan; Li, Xiang; Wang, Yufei; Zhang, ZhiHui; Deng, AnJun; Wang, WenJie; Zhang, Haijing; Qin, Hailin; Wu, LianQiu (Frontiers in Pharmacology, 2020)
Ulcerative colitis is a refractory chronic disease characterized by bloody diarrhea and mucosal or submucosal ulcers. There is an urgent need of new drugs for the treatment of ulcerative colitis. EHLJ7 is a quaternary coptisine derivative. Herein, we explored the therapeutic effect of EHLJ7 on dextran sodium sulfate (DSS)-induced ulcerative colitis (UC) in mice. Results showed that EHLJ7 have good effects on DSS-induced colitis. EHLJ7 significantly improved symptoms induced by DSS including of weight loss, colon contracture, DAI, inflammatory infiltration and so on. Furthermore, results showed that EHLJ7 could enhance short-chain fatty acids (SCFAs) production especially butyric acid, suggesting that EHLJ7 could improve the metabolic disorder of intestinal flora to a certain extent. Further study indicated that EHLJ7 could cooperate with butyrate to exert its anti-ulcerative colitis effect by inhibiting the activation of JAK2/STAT3/SOCS1 pathway. Therefore, EHLJ7 has a potential to be developed as a candidate for the treatment of colitis.